Antiquity and Christianity: considerations on the present and premises for the future - Lourenço, Frederico; Silva, Filipe N. (Romanitas - Revista de Estudos Grecolatinos, 2026)
In this interview, Professor Frederico Lourenço comments on the main challenges concerning the study of Early Christianity in the contemporary world. Questions regarding Frederico Lourenço’s career and his relationship with Antiquity are likewise presented retrospectively by the University of Coimbra professor. Finally, the interview addresses the teaching of classical letters in our own time, both within the university context and beyond.
Keywords: Early Christianity; Antiquity; Roman Empire